Prospect of Fe non-heme on coffee flour made from solid coffee waste: Mini review - Setyobud, Roy Hendroko; Zalizar, Lili; Wahono, Satriyo Krido; Widodo, Wahyu; Wahyudi, Ahmad; Mel, Maizirwan; Prabowo, Bayu; Jani, Yahya; Nugroho, Yogo Adhi; Liwang, Tony; Zaebudin, A (IOP Publishing, 2019)
Coffee flour (CF) from coffee pulp or husk, solid waste of coffee processing have launched in Canada since 2015. This product is claimed as certified of gluten-free, vegan, kosher, paleo, and non-GMO. Coffe flour is stated to contain three times Fe content than fresh spinach (Spinacia oleracea L.). Several receipts of cookies, donuts, and cakes using CF has been introduced as wheat flour substitution. However, the scientific publication of CF impact for health does not appear until August 2018 yet. A review has been carried out using data on Google with a maximum publication age of 15 yr. This Fe non-heme prospect is allegedly unable to be absorbed optimally by the organism. Coffee pulp and husk contain an inhibitor, such as caffeine, polyphenol, calcium, dietary fiber, manganese, magnesium, and zinc; which detain Fe absorption. On the other hand, the promoter/enhancer of Fe absorption such as vitamin C, vitamin A, and amino acid was decreased in CF processing. Several types of research have to be conducted to tackle this problem in Faculty of Medicine and Faculty of Agriculture and Animal Husbandry University Muhammadyah of Malang, Indonesia.